Contributing effects of individual characteristics, behavioural and job-related factors on occurrence of mining-related injuries: A systematic review - Ajith, Michael Mayom; Ghosh, Apurna; Jansz, Janis (IOS PRESS, 2022)
BACKGROUND: Occupational health and safety (OHS) is a complex system due to its three components, namely human, technological and organizational factors. The interplay between the three systems causes workplace accidents and, subsequently, injuries. The body of research currently available demonstrates a disparity in the focus on contributors that cause mining-related injuries beyond the presence of hazards. OBJECTIVE: The aim of this paper was to systematically review and synthesise peer-reviewed published studies that have investigated whether certain individual characteristics, behavioural factors and job-related factors predict mining-related injuries. METHODS: Databases were searched and peer-reviewed publications from 2004 to 2020 were retrieved and analysed. Only 24 from 3073 identified articles were retained for review and synthesis following careful screening. Most identified studies were either cross-sectional or case-control studies, and they were rated as moderate-to-good quality. RESULTS: The review results showed that there is a diverging view in relation to risk factors that cause mining-related injuries. Some publications suggested that old age, male miners, married miners, less educated miners, less experienced miners, alcohol and drug usage, poor working conditions, poor management or supervision, job dissatisfaction and job stress predict injury events while other studies found contradictory relationships or insignificant statistical associations. CONCLUSIONS: Despite the fact that studied risk factors have been well-established in other industries, there is a significant gap in mining that needs further examination. It is imperative that health and safety intervention strategies are devised and implemented for vulnerable groups.